Poverty control policy may affect the transition of geological disaster risk in China - Hengxing Lan; Naiman Tian; Langping Li; Hongjiang Liu; Jianbing Peng; Peng Cui; Chenghu Zhou; Renato Macciotta; John J. Clague (Humanities & Social Sciences Communications, 2022)
Abstract The Chinese government has implemented measures to reduce poverty in the country. Specifically, the Targeted Poverty Alleviation (2013–2020) policy is a set of unique, large-scale and precise poverty control measures undertaken by China in an effort to eliminate absolute poverty. Deeply impoverished areas in the mountainous regions of Southwest China are also particularly prone to geological disasters. A poverty control policy might reduce risk from natural disasters in this region by changing human behaviour. However, it is unclear how the risk might change under the government’s poverty control measures. This paper uses power-law relations and negative binomial regression to analyse primary economic losses from geological disasters in Yunnan Province between 2009 and 2017. The results of the analysis show that the relation between the level of economic development and disaster losses in Yunnan Province changed from an inverted-U shape to a U shape in this period. While direct economic losses from geological disasters are falling, we find that losses in wealthy counties Yunnan Province have not decreased significantly and might even be increasing. In impoverished areas, poverty alleviation policies reduce the economic losses of geological disasters by reducing the vulnerability and exposure, and increasing the resilience. On the contrary, poverty reduction measures promote a concentration of population and wealth in non-poor areas, increasing the vulnerability and exposure, which in turn lead to an increase in direct economic losses from geological disasters. Therefore, in order to consolidate the achievements of poverty alleviation projects, the government needs to pay attention to the transfer of geological disaster risk caused by the policy-driven transformation of human social behaviour.